FAKTOR YANG BERHUBUNGAN DENGAN MINAT WUS DALAM PEMERIKSAAN IVA TEST DI PUSKESMAS - Yusuf, Sulfianti A.; Novika, Revi Gama Hatta; Dewi, Siti Utami; Mahardika, Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Cervical cancer is a type of cancer that develops in the lower part of the uterus that is directly connected to the vagina. Based on an initial survey conducted by researchers in March 2023 by interviewing 15 respondents of women of childbearing age (WUS) showed that there were differences of opinion among respondents regarding their willingness to do the examination. Three respondents expressed interest in taking the VIA examination, while the other five expressed their disinterest because they did not get encouragement or orders from their husbands. The purpose of the study was to determine the factors associated with the interest of wus in the examination of the iva test at the health center. The research design used in this study was cross sectional. The research was conducted in the work area of the Sipori-Pori Inpatient Health Center. The research was conducted in July 2023. The population is all married women of childbearing age in the working area of the Tanjungbalai Sipori-pori Inpatient Health Center in 2022 as many as 4,746 people. The sample amounted to 98 people selected using Stratified Random Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between husband's support (p value: 0.009) and distance to health facilities (p value: 0.017) on WUS's interest in conducting VIA tests. It is recommended for Health Workers to further improve the promotion of the VIA program with communication or IEC on a regular and scheduled basis and for mothers to continue to increase their knowledge about VIA examination through print or electronic media and actively participate in health education provided by health workers.Keywords: Husband Support, Health Facilities, IVA Test.